Plasma cytokine response in mice with bacterial infection - Maja Abram; Darinka Vučković; Branka Wraber; Miljenko Doric (Hindawi Limited, 2000)
Background: Exposure to microorganisms elicts the production of cytokines. These soluble factors enhance several innate immune functions and regulate the ensuing specific immune response aimed at limiting the spread of infection.